The complete mitochondrial genome analysis and phylogenetic position of the short barbeled grunter Hapalogenys nigripinnis (Lobotiformes: Hapalogenyidae) from Jeju island, Korea - Ji, Seung-Chul (Mitochondrial DNA B Resour, 2020)
This study analyzed the complete mitochondrial genome of the short barbeled grunter Hapalogenys nigripinnis (Accession number: MT374064). The complete mitogenome was 16,476 bp long and included 13 protein-coding genes, 22 transfer RNA genes, 2 ribosomal RNA genes, and a control region. Nucleotide composition of the genome was A: 28.70%, T:27.46%, G: 15.73%, and C: 28.11%. All genes were encoded on the H-strand, except for the NADH dehydrogenase subunit (ND6) and 8 tRNA genes. When compared this sequence with the mitogenome of Chinese black grunt, Korean short barbeled grunter showed difference of 64 bp of nucleotide sequence in 20 genes. Phylogenetic tree was constructed using the neighbor-joining (NJ) method and showed the phylogenetic position of the short barbeled grunter in Korea.